(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
Unwanted loneliness is a social phenomenon of increasing prevalence in Spain and other Western countries. Various factors contribute to it, including changes in social organization and family structure. Unwanted loneliness leads to a decrease in emotional links and social contacts, which can lead to the impoverishment of a person’s life world, social isolation, and depression. The main psychopathological clinical conditions in which this “depressive state” appears are: depression, anxiety, obsessive-compulsive disorder, paranoid disorder, eating disorders, substance abuse, and somatization. Unwanted loneliness must be addressed from both a community-social and a health-personal perspective. The contributions of relevant authors on the topic are also reviewed.